Desenvolvimento de modelo téorico-conceitual de apoio à decisão espacial em ambiente de Caatinga - Rocha, Jancerlan Gomes (2020)
In the last decades, discussions about structuring territorial and environmental planning, and its management, are gradually consolidating in the conceptions of State, economy and society as a whole, due to actions aimed at the rational and sustainable use of natural resources. In this way, the institutional actions promoted in the last decades, at the national level, have been focused on the territorial mapping of biomes. These mapping are being produced by the Ministry of Environment (MMA) on generic scales, without the necessary detail to legitimize, for decision makers or local administrative agents, the necessary safety and reliability to put forward planned actions of conservation and sustainable use in the territorial fragments indicated as prioritized or not. In this way, the scale generalization and quality of the data used in these studies have been presenting underestimated territorial portions, specifically with respect to the richness and diversity of the local flora. By the meaning of subsidize decision making, the proposal to develop a theoretical-conceptual model for the definition of priority areas for recovery, conservation and sustainable use emerges as something extremely necessary for systematic environmental planning, mainly in Basic Territorial Unity (UTB), such as Hydrological Basins. Thus the area of study chosen was the Sub-Basin of Paraiba’s River High Course, which area is 6,732.53 km², inserted in the Brazilian semiarid region, specifically in the Caatinga Biome. This research aimed to develop a theoretical-conceptual model driven to support spatial decision making, intended to standardize and integrate certain methods, techniques and technologies such as: Digital Image Processing (PDI); Knowledge Based System; Image Analysis Based on Geographic Objects (GEOBIA); Hierarchical Analysis Process (AHP); floristic diversity indexes – Shannon-Wiener (H'), Simpson’s Dominance (S) and Maximum Diversity In (S); IDW and Kriging geostatistical interpolation, using a weighted linear combination; the chemical parameters of soil fertility - pH (H2O) and available phosphorus (P); and bioclimatic. All this logic was built according to the current environmental legislation, having as spatial support the SiCAR basis of Space Decision Support System (SADE). A developed methodology allowed for digital cartographic products (Cartographic Accuracy Standard (PEC) with standard error of 15.0 meters, in a scale compatible with the scale of 1: 25.000, and a sampling error from forestry inventory sampling error of 5.7% - acceptable or confident probability value (%). Some results showed that 69% of the entire sub-basin is covered by Remnant of Native Vegetation, where about 11.67% of this total corresponds to typology stratum of Opened Shrubby Low Caatinga (T1). Furthermore, around 31.99% of the total area of the sub-basin is not suitable for environmental regularization of the Legal Reserve deficit situation. The data also show that around 8.60% of the entire area of study presents a high to very high environmental fragility, and that about 69.70% of the soils of the sub basin present classes (very low to low) of Phosphorus content (P) available in soil. While areas with the purpose of conservation and sustainable use corresponds to, respectively, 15.14% and 41.30% of all hydrographic basin. The most alarming data refers to the areas that will be the target of vegetal recovery, located in Legal Reserves and Permanent Preservation Areas, corresponding to 6.60% of all hydrographic basin, which amounts to 44,399.99 hectares.